The effect of interspecific hybridization on spermatogenesis indicators in males of the genus Ovis - Volkova L.A.; Volkova N.A. (Ветеринария и кормление)
Interspecific hybridization of domestic sheep with related wild species is considered as one of the promising directions in animal husbandry. Obtaining, breeding and use of hybrid animals in breeding programs requires a more in-depth study of their physiological characteristics, primarily their reproductive qualities. The aim of the study was to investigate age-related features of spermatogenesis in males of the genus Ovis during interspecific hybridization. The objects of the research were: interspecific hybrids obtained through a series of crosses of domestic sheep of two breeds - Romanov and Katahdin - with related wild species - argali and mouflon (n=8); rams of the Romanov breed (n=8) and Katahdin (n=6). Histological studies of the testicular structure from hybrid and purebred animals were carried out at the ages of 6 and 12 months. The following parameters were studied: diameter and area (cross section) of seminiferous tubules, number of seminiferous tubules per unit area of histological section, and composition of spermatozoa cells in them. Purebred Romanov rams and Katahdin rams were superior to male interspecies hybrids in terms of the development of seminiferous tubules of the testes and the number of spermatogenic cells in them. Analysis of the composition of cells in the seminiferous tubules of the testes of the studied males showed that in hybrid animals at the age of 6 months, the cells of the epitheliospermatogenic layer were represented mainly by Sertoli cells, spermatogonia and spermatocytes. Spermatids were detected in individual seminiferous tubules. At the age of 12 months, all cell types were present in the seminiferous tubules, but the presence of sperm in the lumen of the seminiferous tubules was insignificant. All types of spermatogenic cells, including mature germ cells of sperm at both 6 and 12 months of age, were identified in the seminiferous tubules of the testes of purebred animals. The data obtained indicate a later sexual maturation of hybrid animals compared to the original maternal breeds (Romanov and Katahdin breeds), which must be considered when breeding and selecting these animals.